IEEE International Conference on Advanced Learning Technologies, 2004. Proceedings.
DOI: 10.1109/icalt.2004.1357642
|View full text |Cite
|
Sign up to set email alerts
|

Learning with lecture recordings: key issues for end-users

Abstract: Computer-based recording of live presentations has become a widespread method of producing learning materials in both higher education and companies. The success of such contents depends on their acceptance by the end-users working with the materials. From their point of view, the support of certain features and, thus, the choice of formats used for network delivery and replay are crucial issues. We present a list of key factors from the end-user's perspective and report on a user study carried out to evaluate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 2 publications
0
22
0
Order By: Relevance
“…A chi-squared test for independence found the differences between Non-Users and users of some video (Low Users + High Users) was not significant (this test eliminated the single "poor" response because of the inflated influence of small response counts on the chi-squared test). Although video quality was reported as a substantial barrier to the use of recorded lectures in some studies (Lauer et al, 2004), results suggested that the quality of the online videos in this study was not a factor in the choice to watch the lecture on video rather than attending in person.…”
Section: Perceived Quality Of Video Lecturesmentioning
confidence: 54%
See 1 more Smart Citation
“…A chi-squared test for independence found the differences between Non-Users and users of some video (Low Users + High Users) was not significant (this test eliminated the single "poor" response because of the inflated influence of small response counts on the chi-squared test). Although video quality was reported as a substantial barrier to the use of recorded lectures in some studies (Lauer et al, 2004), results suggested that the quality of the online videos in this study was not a factor in the choice to watch the lecture on video rather than attending in person.…”
Section: Perceived Quality Of Video Lecturesmentioning
confidence: 54%
“…To address concerns regarding student perceptions of recorded video quality (Lauer, Muller, & Trahasch, 2004), the students were given a short survey about the general quality of the recorded videos approximately three-quarters of the way through the semester, or at the mid-point of the video option. This survey was given under the condition that individual student responses would remain confidential and not be communicated to course personnel.…”
Section: Description Of Experimentsmentioning
confidence: 99%
“…Some studies found that it has little to no impact (Chandra 2007 ;von Konsky, Ivins, and Grible 2009 ) and others showed a modest decline in the percentage of students who attend class (Billings-Gagliardi and Mazor 2007 ). In other research, it was found that about one third of students would opt for video-only lectures, if given the choice (Lauer, Müller, and Trahasch 2004 ). In general, we expect students to be strategic, attending class when it proves benefi cial and using this resource when it provides the best payoff .…”
Section: Concerns About Attendancementioning
confidence: 99%
“…Recordings can be thought of best as a resource that some students take advantage of when it is benefi cial to them. Moreover, students are strategic when determining which lectures to watch and for how long (Billings-Gagliardi and Mazor 2007 ;Gosper et al 2007;Green, Pinder-Grover, and Millunchick 2012 ;Lauer, Müller, and Trahasch 2004 ;Owston, Lupshenyuk, and Wideman 2011 ;von Konsky, Ivins, and Gribble 2009 ). Specifically, students use recordings to study for exams (Chandra 2007 ;Gosper et al 2007), to catch up on lectures they may have missed (Gosper et al 2007;von Konsky, Ivins, and Gribble 2009 ), and to review material that they fi nd diffi cult to understand (Green, Pinder-Grover, and Millunchick 2012 ;Owston, Lupshenyuk, and Wideman 2011 ).…”
Section: How Often Are the Recordings Used?mentioning
confidence: 99%
“…For example, the benefits of interactive devices [1], [2], [3] or systems that assist interactive face-to-face sessions have been presented in [4], [5] and [6]. Also, the contribution of lecture recording has been focused within the last few years and evaluation results have been presented in [7], [8] and [9], for instance.…”
Section: Introductionmentioning
confidence: 99%